Transformation and Effects of Human Rights Protection on Determining Corruption Suspects as a Pretrial Object under the Indonesian Criminal Justice System (Lex Scientia Law Review, 2024)
This study explores the transformation of human rights understanding and legal enforcement within the Indonesian criminal justice system, focusing on expanding the scope of pre-trial elements. The debate centers around balancing citizens' rights to protection with the public’s demand for legal certainty under the Indonesian Criminal Code (KUHP). This research presents a coherent approach to address this dilemma, aiming to establish legal certainty and justice in line with Article 28 of Indonesia’s 1945 Constitution. The central legal issue is the lack of clarity and certainty in the determination of suspects, particularly in corruption cases, due to legal gaps in the Indonesian Criminal Procedure Code (KUHAP). This uncertainty prevents victim compensation and rehabilitation, making it impossible for victims to seek legal redress. The study argues for a review of Law No. 8 of 1981 to strengthen victim protection in such cases. Findings reveal the crucial role of human rights in reforming pre-trial procedures, notably the inclusion of suspect determination as a pre-trial element under Constitutional Court Decision No. 21/PUU-XII/2014. This shift ensures that suspects’ rights are safeguarded, especially in corruption cases, aligning with Indonesia's obligation to uphold human rights and minimize unjust detentions. The study’s contribution extends to both national and global contexts, offering insights into the importance of legal reforms that safeguard human rights while ensuring justice and legal certainty. It recommends that the government implement legal measures to provide compensation and rehabilitation for victims of wrongful corruption suspect determinations.